Identifying Risk Factors for Anthracycline Chemotherapy-induced Phlebitis in Women with Breast Cancer: An Observational Study. Issue 4 (April 2021) - Roberts, R.; Borley, A.; Hanna, L.; Dolan, G.; Ganesh, S.; Williams, E.M.
Abstract: Aims: Anthracycline chemotherapy administered via a peripheral cannula results in severe anthracycline chemotherapy-induced phlebitis (ACIP) in about 20–30% of patients. Administering chemotherapy via a central venous catheter (CVC) prevents ACIP. However, CVCs are associated with an increased risk of thrombosis and sepsis. Our aim was to identify risk factors associated with severe ACIP and to provide evidence about the individual risk of developing symptoms. Materials and methods: A prospective observational study of 263 women with breast cancer receiving peripheral administration of anthracycline chemotherapy at a UK cancer centre was conducted between May 2016 and January 2018. Data were collected at baseline and every 3 weeks following each chemotherapy treatment, using both healthcare professional- and participant-reported symptom assessments. Results: After three cycles of chemotherapy, 27% of participants experienced severe ACIP. Factors associated with symptom severity were identified as: arm used for chemotherapy administration, epirubicin dose, age, pre-existing hypertension, comorbidity, ethnic group and pain during chemotherapy administration. The sequence of arm used for chemotherapy administration was the single most significant factor ( P < 0.001). When alternating arms were used no other risk factor was influential. Where alternating arms were not used, younger age and higher dose were associated with higher-grade symptoms, with age being more influential than dose. The cumulative effect of increasing symptom severity with repeated cycles was also identified ( P < 0.001). Conclusion: It is recommended that a CVC is not routinely required for women with breast cancer who have not undergone an axillary node clearance and receive chemotherapy in alternate arms. The need for a CVC for women who are planned to receive all anthracycline chemotherapy cycles in the same arm should be assessed in the light of peripheral venous access assessment and the key risk factors of age, dose and number of cycles. Highlights: Peripheral administration of anthracycline chemotherapy can result in phlebitis. Phlebitis severity increases with the number of cycles administered. After three cycles of epirubicin 27% of patients experienced high-grade symptoms. Alternating arms for administration significantly reduces the risk of phlebitis. Younger age and higher doses are key risk factors for anthracycline phlebitis.